Optimising BTP ligands by tuning their basicity - Trumm, Sascha; Wipff, G.; Geist, Andreas; Panak, Petra; Fanghänel, Thomas (Radiochimica acta, 2011)
A novel approach for the optimisation of extractants for the actinide(III)/lanthanide(III) separation is presented. Two BTP ligands are synthesised carrying OMe or Cl moieties on the pyridine ring, thus altering the electronic structure of the aromatic system. The influence of functionalisation on the ligand basicity is determined both spectroscopically and by quantum chemical calculations. Furthermore, we show that both distribution ratios and separation factors for Am(III)/Eu(III) separation increase upon increase of ligand basicity.